GENDER DISPARITY IN PREVALENCE OF TUBERCULOSIS IN REGION VARNA IN 2012. - Gabriela Tsankova; Violina Kaludova; Emilia Georgieva; Neli Ermenlieva (Peytchinski Publishing, 2014)
Aim: To assess the gender differences among suspected pulmonary tuberculosis patients undergoing diagnostic sputum smear microscopy. Materials and methods: The study covered the patients with TBC diagnosed and treated in the region of Varna during 2012. Data have been gathered by the Laboratory of Microbiology at the Specialized Hospital of Pneumologic and Phthisiatric Diseases of Varna Ltd. Results: Gender and age are both traditionally known variables in terms of incidence and prevalence of pulmonary tuberculosis. The patients were classified into various groups according to gender and age. In 2012 the number of the men suffering from tuberculosis is repeatedly greater than those concerning the women (42 men to 29 women from 2012). This is probably due to the numerous risk factors among men, but biological mechanisms may actually account for a significant part of this difference between male and female susceptibility to TB.